2021
DOI: 10.1016/j.heliyon.2021.e08179
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of FOXN3-AS1 in invasive ductal carcinoma of breast cancer patients

Abstract: Oncogenic and tumor-suppressive roles of long non-coding RNA make them an appropriate target for expression analysis in cancer studies. In this study, we selected two lncRNAs (EMX2OS and FOXN3-AS1) that are resided near the GWAS-identified SNPs for breast cancer (rs2901157 and rs141061110). These transcripts have been identified in different cancer types as either oncogenes or tumor suppressors. In the present investigation, we aimed to quantify the expression level of EMX2OS and FOXN3-AS1 in 44 breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, we found that CYP1B1-AS1 had significantly higher expression levels in breast cancer tissues than in normal tissue adjacent to the cancer. In recent years, the long-stranded non-coding RNA CYP1B1-AS1 is gaining attention as an important factor in the development of tumors, such as breast cancer and glioblastoma ( Molaei Ramshe et al ., 2021 ; Ye et al ., 2021 ). A study noted that CYP1B1 was identified as a regulatory target of CYP1B1-AS1 ( Ye et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that CYP1B1-AS1 had significantly higher expression levels in breast cancer tissues than in normal tissue adjacent to the cancer. In recent years, the long-stranded non-coding RNA CYP1B1-AS1 is gaining attention as an important factor in the development of tumors, such as breast cancer and glioblastoma ( Molaei Ramshe et al ., 2021 ; Ye et al ., 2021 ). A study noted that CYP1B1 was identified as a regulatory target of CYP1B1-AS1 ( Ye et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these CRlncRNAs, depletion of DIRC3-AS1 could increase the anchorage-independent growth, which means to malignant transformation, and reduce the survival time of melanoma 29 . Besides, the expression of FOXN3-AS1 was signi cantly elevated in breast cancer samples and associated with the tumor size 30 . Furthermore, LINC00682 correlated with the recurrence of hepatocellular carcinoma 31 .…”
Section: Discussionmentioning
confidence: 99%